The potential capability of treated perlite for removal of penta chloro nitrobenzene - Gulen, Jale; Deler, Omer (WALTER DE GRUYTER GMBH, 2024)
Perlite is an example of clayey type geologic mineral. Perlite is a cheap and abundant adsorbent and it can be used for versatile applications in food, pharmacy and chemistry industries. Perlite was chosen for the removal of penta chloro nitrobenzene (PCNB) pesticide. This pesticide is used for the control of fungi species in farming commonly. Adsorbent surface area and pore volumes were determined as 288.15 m(2)/g and 78.24 cm(3)/g (BET method). The characteristics of the adsorbent were furnished by evaluating the SEM and FTIR images. The adsorption equilibrium was reached in 80 min. Initial adsorbate concentration and pH of the medium were also investigated from this point of view. The experimental data were evaluated with proper isotherm models such as Langmuir, Freundlich and Halsey. Langmuir and Freundlich isotherms give the best results. Monolayer capacity was found as 238.095 mg/g. The kinetic mechanisms of the phenomon was analyzed by employing the pseudo first and second order models. Pseudo first order kinetic results were better than the second one with the higher regression coefficients and close experimental and calculated uptake values. Those values were found as 0.615 and 0.6587 mg/g for 1 mu g/mL aqueous pesticide solution. Activation energy was found approximately 5094 J/mol which was shown a physisorption mechanism of the adsorption. Activation energy is also employed for interpreting the sticking probability factor. The thermodynamic of adsorption were also evaluated and found as -2.385 J/g at the room temperature. The negative Gibbs energy shows the feasibility and spontaneous nature of PCNB removal on perlite.
Keywords: isotherms; kinetic; perlite; pesticide; thermodynamic; FACILE SYNTHESIS; SUPERCAPACITOR; NANOPARTICLES; NANORODS; Chemistry